2019
DOI: 10.1186/s13048-019-0558-5
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in cancer: new insights into functions and implications in ovarian cancer

Abstract: Circular RNAs (circRNAs) are a class of long non-coding RNAs (lncRNAs) which have a circular and closed loop structure. They are ubiquitous, stable, conserved and diverse RNA molecules with a range of activities such as translation and splicing regulation, which are able to interacting with RNA-binding proteins and specially miRNA sponge. The expression patterns of the circRNAs exhibited tissue specificity and also, step and stage specificity. Accumulating evidences approved the critical role of circular RNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 102 publications
(91 reference statements)
2
74
0
Order By: Relevance
“…In fact, the non-coding RNAs represent the RNA, which would not encode a protein and thus may be categorized into multiple groups like the long non-coding RNAs (lncRNAs = above 200 nucleotides in length) and small non-coding RNAs (like microRNAs = approximately 19 to 22 nucleotides in length) [137][138][139][140][141]. Finally, it has been found that that microRNAs (miRNAs) regulated translational effectiveness or stability of the targeted mRNAs via interactions with 3′-un-translated region (3′-UTR) of the respective targets [142][143][144][145][146][147].…”
Section: Micrornasmentioning
confidence: 99%
“…In fact, the non-coding RNAs represent the RNA, which would not encode a protein and thus may be categorized into multiple groups like the long non-coding RNAs (lncRNAs = above 200 nucleotides in length) and small non-coding RNAs (like microRNAs = approximately 19 to 22 nucleotides in length) [137][138][139][140][141]. Finally, it has been found that that microRNAs (miRNAs) regulated translational effectiveness or stability of the targeted mRNAs via interactions with 3′-un-translated region (3′-UTR) of the respective targets [142][143][144][145][146][147].…”
Section: Micrornasmentioning
confidence: 99%
“…In recent years, numerous studies focused on differentially expressed circRNAs and their function in this malignancy indicating that circRNAs may act as potentially novel biomarkers or therapeutic agents in this cancer type. 198 Increasing number of circRNAs have been reported to be involved in the progression and tumorigenesis of ovarian cancer. One study revealed that circPUM1 promoted cell proliferation, migration, invasion, and metastasis through increased the expression of nuclear factor kappa B (NF-κB) and matrix metallopeptidase 2 (MMP2) by sponging miR-615-5p and miR-6753-5p in ovarian cancer cells.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Cancer is still one of the increasing challenges worldwide (Shabaninejad et al, 2019; Tamtaji et al, 2020). The field of cancer therapy has undergone a number of changes.…”
Section: Anti‐tumor Activity Of Curcuminmentioning
confidence: 99%